Children Dealing with Parental Absences during Wartime in Vietnamese Literature: A Study of ‘Southern Forestland’ by Doan Gioi, ‘Absent Mother’ by Nguyen Thi, and ‘The Ivory Comb’ by Nguyen Quang Sang - Trinh Dang Nguyen Huong, (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
War is an extraordinary and brutal condition of life. Surviving war is difficult for anyone, especially for children. Even in times of peace, children depend heavily on the care, love, and nurturing of adults. Can children truly live, retain their spirited innocence, and grow under the harsh conditions of war? What kind of beauty emerges from children who grow up without one or both parents during wartime? How do these children survive, sustain faith in the future, and learn to mature amidst the devastation of their country? This article seeks to answer these questions by analyzing three literary narratives about children in families lacking fathers, mothers, or both due to war: The Ivory Comb [Chiếc lược ngà] by Nguyen Quang Sang, Absent Mother [Mẹ vắng nhà] by Nguyen Thi, and Southern Forestland [Đất rừng phương Nam] by Doan Gioi. Utilizing discourse analysis, comparative methods, and an interdisciplinary approach, the article highlights how Vietnamese children’s literature has contributed to representing war from children's perspectives. By portraying wartime from the lens of parental absence and the difficult process of growing up, Vietnamese writers have shown that children possess their own perspectives and make independent choices to adapt and mature under extreme conditions.Received 15th December 2024; Revised 5th March 2025; Accepted 17th April 2025